2018
DOI: 10.1177/0533316418764392
|View full text |Cite
|
Sign up to set email alerts
|

Four modalities of the experience of others in groups

Abstract: The ways in which group members experience and interact with one another has been explored in philosophy from Greek antiquity to the present. In modern European philosophy, beginning with the Enlightenment, the problem of 'the Other' has been taken up by empirical, idealist, phenomenological and existential philosophers. Based on such philosophical discourse, this article presents a fourfold schema of 'modalities' through which people acquire knowledge of one another in groups. The four modalities are as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In his idiosyncratic contribution to our thinking about persons, relationships, and social entities, Victor Schermer (2018), a former Foulkes Lecturer and a well-known contributor to the literature in group analysis and psychoanalytical group therapy in the United States and in England, abstracts from the magma four modalities of the experience of others in groups: mind, body, gaze, and face. Schermer provides many examples of these processes and cites a range of sources of his ideas, which has an integrative quality.…”
mentioning
confidence: 99%
“…In his idiosyncratic contribution to our thinking about persons, relationships, and social entities, Victor Schermer (2018), a former Foulkes Lecturer and a well-known contributor to the literature in group analysis and psychoanalytical group therapy in the United States and in England, abstracts from the magma four modalities of the experience of others in groups: mind, body, gaze, and face. Schermer provides many examples of these processes and cites a range of sources of his ideas, which has an integrative quality.…”
mentioning
confidence: 99%
“…Some (in fact from Socrates onward) have also suggested that philosophy can have therapeutic as well as investigative aspects. Appreciating the role of philosophy in both these senses, I read Vic Schermer's (2018) article with much interest, intrigued by his avowed aim to open questions around the 'ways in which group members get to know those who are initially strangers to them, and who present them with their mystery' (p. xx). I am glad he uses that word, 'mystery', with positive implications rather than as a quality that should be on the way to being overcome or resolved.…”
mentioning
confidence: 99%
“…I was delighted to be invited to respond to Vic Schermer's article (Schermer, 2018). I have long been aware of his significant contribution to group psychotherapy (including group analysis)-Object Relations, the Self and the Group (1994Group ( [1987) (written with Charles Ashbach) and Ring of Fire (1994) (edited with Malcolm Pines) having occupied a place on my shelves even before training as a group analyst.…”
mentioning
confidence: 99%